Sickness and Treatment: A Situation Analysis among the Garments Workers (Anwer Khan Modern Medical College Journal, 2013)
This was a descriptive type of cross sectional study among 522 garments workers as  respondents. It was aimed to identify morbidity pattern, duration of illness among garments  workers and also to determine treatment seeking behavior during illness. The socio-demographic  characteristics of the respondents were the points of investigations.  It was revealed from the findings that the mean age of the respondents were 23.1years. They  were mostly female (80%) and married (60%). About 60% respondents were found primarily  educated and no one found illiterate. 90% respondents were found from nucleated family. The  study shows 79% respondents were suffering from illness during the last 02 months and majority  suffers (18.6%) and (43.6%) were found among 26-30 years age groups and 21-25 years age  groups respectively. However, female sufferers were more (33.6%) than male (10%) in the 21-  25 years age groups. Moreover about 42% respondents were suffering for 1-2 weeks and 28.8  are suffering for less than 02 weeks. On the otherhands, Loose motion, Cough, and  Breathlessness were found prominent sign/symptoms among 38%, 29%, 28% sufferers  respectively. Diarrhoea, Common cold and Respiratory Tract Infections were found as  predominant diagnosis among 40.5%, 22.5% & 15.1% respondents respectively. Nevertheless  majority 56% were seeking treatment from LMAF doctors. Conclusion: The study findings  highlight awareness program among factory owners and garments workers towards preventing  infectious and chronic diseases as well as to undertake modern scientific treatment. Improved  health care facilities in the garments factory may be considered for early detection and treatment  of cases to avoid complications. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13678 AKMMC J 2013: 4(1): 10-14